A load identification method for the grinding damage induced stress (GDIS) distribution in silicon wafers. (August 2016) - Zhou, Ping; Xu, Shance; Wang, Ziguang; Yan, Ying; Kang, Renke; Guo, Dongming
Abstract: Subsurface damage (SSD) and grinding damage induced stress (GDIS) result in deformation and strength degradation of a ground silicon wafer. The Stoney equation is widely used as a non-destructive method for finding GDIS in a silicon wafer prepared by the rotational grinding method. However, the basic assumptions of the Stoney equation ignore the detailed information on the GDIS in a ground wafer. In this paper, a new method is proposed for analyzing GDIS distribution in a silicon wafer thinned by grinding. The wafer is diced into small chips for identification of stress state with a load identification method. The results show that the stresses are not independent of the direction as assumed in the Stoney equation, and the ratio of the two principal stresses in the damage layer is approximately 2:3 under the grinding conditions of a #3000 diamond wheel with a spark-out time of 5 s. Moreover, the principal stress direction is obviously aligned with the grinding direction but independent of the crystalline orientation. The SSD is observed with a Transmission Electron Microscope (TEM), which shows numerous plane defects parallel to the {111} planes. It can be deduced from the results that the defects are non-uniformly distributed in the subsurface with their directions in the slip direction of the grinding abrasives. However, the principal stresses at any points have their respective values close to each other. The results of this study are unique and unexpected. Highlights: Proposing a new method for analyzing the GDIS distribution in silicon wafers; The ratio of the two principal stresses in the SSD layer is approximately 2:3; The principal stress direction is obviously aligned with the grinding direction; The GDIS distribution is independent of the crystalline orientation;